Detection of Her 2/Neu Equivocal Immunochemistry by Fish in Breast Carcinoma – A Study from Single Tertiary Care Hospital - Momota, Naiding; Biswadeep, Choudhury; Sumita, Duttagupta; Biman, Deuri; Nivedita, Dasgupta; Saurav, Deb; Jyotika, Sharma (Archives of Clinical and Biomedical Research, 2023)
Background: Both IHC and FISH were used for Human epidermal growth factor receptor-2 status testing but for confirmation of all equivocal specimens having +2 score (Her-2 status) in IHC, the FISH method is used. We report a prospective study to reflect the concordance between IHC and FISH in Her-2 status confirmation. Methods: Sixty cases of breast carcinoma tissue samples tested by IHC and scored as 0, 1+, 2+, and 3+ and were further analyzed by FISH using a commercially available PathVysion HER-2 probe kit, and the FISH findings of equivocal samples were compared with IHC test results. Results: A Total of sixty breast carcinoma patients' tissue sections were tested by the Immunohistochemistry method and out of that fifteen samples (9%) were found HER-2 neu positive with +3 Score and Forty samples (24%) were found negative with 0 to +1 score and five samples (3%) were found equivocal I.e., +2 score. The remaining 05 samples were tested by FISH for Her-2 Status confirmation. And all equivocal samples were found negative on the FISH assay. Conclusion: The Immunohistochemistry test can be used to screen the HER-2 status, and after IHC assay FISH can be used as a confirmatory test for all Her-2 borderline cases. And only those equivocal cases or borderline cases with Her-2 status of IHC 2+ score should be confirmed with the FISH assay.